FACTORS ASSOCIATED WITH INFORMED CONSENT AMONG PERSONS WITH DEMENTIA: THE DEMENTIA BEHAVIOR STUDY. (16th November 2018) - Parker, L; Marx, K; Gitlin, L
Abstract: Consideration of factors associated with obtaining informed consent from persons with dementia are critical to enrolling them into research. Using baseline data from the Dementia Behavior Study, the aim of the study was to provide a descriptive analysis of characteristics associated with the ability to provide inform consent among 239 PWD. The PWD's ability to provide informed consent was determined by a series of questions inserted at critical points in the written consent form (purpose, randomization, risks, benefits, voluntary participation). Interviewers marked if the response was correct or incorrect. The PWD was deemed unable to provide informed consent if they had any incorrect response after two attempts. Thirty-four percent (n = 82) of the PWD were able to provide consent. Among those who provided consent, 72% were White (p<0.05). Of those persons able to provide consent, 2.5% had a MMSE from 0–9, 41.2% of had a MMSE from 10–18, 40% had a MMSE from 19–24, and 16.2% had a MMSE>24 (p<0.001). On average, persons who provided consent had 2 hours a day for assistance with activities of daily living, 5 hours for assistance with instrumental activities of daily living and 6 IADLs. Interestingly, Neuropsychiatric Inventory Behaviors were not a characteristics associated with the ability of being able to provide informed consent. Results from this study show that individuals with a diagnosis of dementia may be able to provide informed consents for their participation in a research study and should be provided with the opportunity when possible.